2010
DOI: 10.1002/pbc.22608
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of an educational interactive CD‐ROM for teens with cancer

Abstract: Background Cancer is the number one disease killer of children and adolescents in North America. For adolescents, this diagnosis comes at a particularly vulnerable stage. Educating adolescents with cancer from diagnosis through treatment teaches and empowers them. Increasing evidence shows that these adolescents want more information. Few educational tools exist for young cancer patients; none are interactive; therefore, a CD‐ROM was developed to meet this need. Procedure Animation, voiceover, music, videos, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
79
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(85 citation statements)
references
References 22 publications
1
79
0
5
Order By: Relevance
“…Jones et al [42] created a CD-ROM to empower cancer patients to "beat" cancer and return to a productive life. The CD contains several topics (e.g.…”
Section: Technology-based Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Jones et al [42] created a CD-ROM to empower cancer patients to "beat" cancer and return to a productive life. The CD contains several topics (e.g.…”
Section: Technology-based Interventionsmentioning
confidence: 99%
“…Six studies [39][40][41][42][43][44] examined the effects of technologybased interventions. The majority of these studies used multiple outcome parameters.…”
Section: Technology-based Interventionsmentioning
confidence: 99%
“…2009) reported that children and young people were involved in the development of the intervention but this was only through consultation, not collaboration stated user involvement was through collaboration but the text describes more consultation than collaboration). Finally, only 8 (30%) studies reported pilot testing the intervention and/or study design Holden et al, 2000;Homer et al, 2000;Johnson et al, 2001;Jones et al, 2010;McPherson et al, 2006;Rubin et al, 1986;Whittemore et al, 2012). Two studies did not report conducting a pilot study although in the process of the literature search publications of pilot studies were identified (Franklin, Waller, Pagliari, & Greene, 2003;Joshi, Lichenstein, Rafei, Bakar, & Arora, 2007).…”
Section: Papers Included In Review (N=27)mentioning
confidence: 94%
“…Seven (26%) of the included papers Johnson et al, 2001;Jones et al, 2010;McPherson et al, 2006;Mulvaney et al, 2010;Stinson et al, 2010;Zorc et al, (17) Not relevant (13) Intervention does not involve technology (11) Prevention/health promotion (11) Intervention for parents (7) Discussion paper (6) Review paper (4) Conference abstract (1) Intervention for siblings (1) Studies eligible for inclusion in review (n = 40)…”
Section: Identified Studiesmentioning
confidence: 99%
See 1 more Smart Citation